Pengaruh perputaran persediaan, Capital Intensity, dan Leverage terhadap Tax Avoidance dengan ukuran perusahaan sebagai variabel moderasi - Hermanto, Hermanto; Puspita, Intan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of inventory turnover, capital intensity, and leverage on tax avoidance with firm size as a moderating variable. In this study using quantitative research methods. This research uses data obtained from food and beverage companies listed on the Indonesia Stock Exchange from 2018-2021, this study used 160 samples from 40 companies using the STATA data processing program application with the purposive sampling technique. Based on the research that has been done, the results are that inventory turnover has a negative effect on tax avoidance, the capital intensity does not affect tax avoidance, leverage has a positive impact on tax avoidance, and company size can moderate inventory turnover on tax avoidance, company size is unable to moderate capital intensity on tax avoidance, and company size negatively moderate leverage on tax avoidance.